Dékor of konteks? - Die verdiskontering van sosio-historiese gegewens in interpretasie van 'n Nuwe Testament-teks vir die prediking en pastoraat, geillustreer aan die hand van die 1 Petrus-brief - Rensburg, F. Janse van (Verbum et ecclesia, 2000)
Decor or context? The utilisation of socio-historic data in the interpretation of a New Testament text for the preaching and pastorate, illustrated with First Peter The article proposes, from a reformed perspective, a method for the valid utilisation of the socio-historic data of a New Testament book in the process of interpretation. Firstly a synoptic indication of the difference between a "background" and a "context" approach is given, as well as of a socio-historic and the socio-scientific approach, and of an emic and an etic approach, in each case motivating the choice for a specific approach. The sources for the determination of the sociohistoric context of the New Testament are indicated, and the preference for literary sources motivated. The theological perspective from which the utilisation is done, is defined, specifically the relation between the Bible text and other sources, in the light of Articles 2-7 of the Belgic Confession. The preferred view of text and society is given, as well as the reasons for the preference in each case. All of this is done, using First Peter as illustration.